Retrospective Evaluation of a Restrictive Transfusion Strategy in Older Adults with Hip Fracture. Issue 6 (20th April 2018) - Zerah, Lorene; Dourthe, Lucile; Cohen‐Bittan, Judith; Verny, Marc; Raux, Mathieu; Mézière, Anthony; Khiami, Frédéric; Tourette, Cendrine; Neri, Christian; Le Manach, Yannick; Riou, Bruno; Vallet, Hélène; et al.
Abstract : Objectives: To compare the association between a restrictive transfusion strategy and cardiovascular complications during hospitalization for hip fracture with the association between a liberal transfusion strategy and cardiovascular complications, accounting for all transfusions from the emergency department to postacute rehabilitation settings. Design: Retrospective study. Setting: Perioperative geriatric care unit. Participants: All individuals aged 70 and older admitted to the emergency department for hip fracture and hospitalized in our perioperative geriatric care unit (N=667; n=193 in the liberal transfusion group, n=474 in the restrictive transfusion group) from July 2009 to April 2016. Intervention: A restrictive transfusion strategy (hemoglobin level threshold ≥8 g/dL or symptoms) used from January 2012 to April 2016 was compared with the liberal transfusion strategy (hemoglobin level threshold ≥10 g/dL) used from July 2009 to December 2011. Measurements: Primary endpoint was in‐hospital acute cardiovascular complications (heart failure, myocardial infarction, atrial fibrillation or stroke). Results: The change to a restrictive transfusion strategy was associated with fewer acute cardiovascular complications (odds ratio=0.45, 95% confidence interval (CI)=0.31–0.67, p<.001), without any noticeable difference in in‐hospital or 6‐month mortality. The change also led to a reduction in packed red blood cell units used per participant (median 1, interquartile range (IQR) 0–2 in restrictive vs median 2, IQR 0–3 in liberal transfusion strategy, P<.001). In rehabilitation settings, the frequency of transfusion was greater with the restrictive transfusion strategy than the liberal transfusion strategy (18% vs 9%, P<.001). Conclusion: A restrictive transfusion strategy in older adults with hip fracture was found to be safe and was associated with fewer cardiovascular complications but more transfusions in rehabilitation settings. Prospective studies are needed to confirm these findings.